Analysis of Capital Expenditure Financing Through the Issuance of Local Debt Securities (Bond) - Sudaryanto, Edy; Ramlan, Ramlan; Maharani, Lastri; Dwiyani, Ervina (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2026)
Law Number 23 of 2014 on Regional Government mandates that regional governments play a very important role in determining the success of creating independence, but in practice, regional governments encounter limitations in funding sources. Most regencies and cities are highly dependent on transfer funds provided by the central government to the regions. Other sources of income, namely Regional Original Revenue (PAD), are very limited, as this revenue has been authorized by the central government to implement regional autonomy. By delegating this authority, the government hopes that the West Java provincial government will be able to explore the potential of its region to finance its development, thereby reducing its dependence on the central government. This study aims to analyze the feasibility of the West Java Provincial Government issuing regional debt securities (bonds) to finance infrastructure development through capital expenditure that can boost the welfare of the people in West Java Province. This study uses a descriptive qualitative research design with an analytical approach. The results indicate that the West Java Provincial Government is highly eligible to issue regional debt securities (bonds) to finance its infrastructure development through capital expenditure.